2020
DOI: 10.3390/ani10040605
|View full text |Cite
|
Sign up to set email alerts
|

Feather Corticosterone Measurements of Greater Flamingos Living under Different Forms of Flight Restraint

Abstract: Deflighting zoo birds is a practice that receives increasing criticism due to its presumed incompatibility with animal welfare. To our knowledge, this is the first approach to address this problem in a scientific way. To do this, we compared feather corticosterone (CORTf) from Greater Flamingos (Phoenicopterus roseus, n = 151) of different flight status (i.e., pinioned, feather clipped, airworthy) from twelve different zoological institutions. To complement the hormone measurements, behavioral observations (sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…To assess the relevance of the within-individual variation (median 15.6% for Anser, 17.8% for Anas), this and the maximum values (6.99 pg/mm in Anser, 4.28 pg/mm in Anas) must be compared to values from animals kept under different husbandry conditions. Since there are no values from stressed Anser and stressed Anas available in the literature, we discuss results of a study performed on Greater Flamingos for an estimation [48]. Stress was expected in one group due to repeated attacks by cranes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To assess the relevance of the within-individual variation (median 15.6% for Anser, 17.8% for Anas), this and the maximum values (6.99 pg/mm in Anser, 4.28 pg/mm in Anas) must be compared to values from animals kept under different husbandry conditions. Since there are no values from stressed Anser and stressed Anas available in the literature, we discuss results of a study performed on Greater Flamingos for an estimation [48]. Stress was expected in one group due to repeated attacks by cranes.…”
Section: Discussionmentioning
confidence: 98%
“…Concerning this topic, ongoing studies, as well as currently published studies, focus on the evaluation of deflighting zoo birds, the comparison between different husbandries and the welfare implications. These deal with the species Greater Flamingo (Phoenicopterus roseus) [48] and Great White Pelican (Pelecanus onocrotalus) (ongoing study). The planning, structure and realization of research projects compared to these could also be expanded and simplified with this non-invasive sampling method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done either to prevent the bird from flying away and escaping or, in an attempt to keep the bird safe, as the home where they live is dangerous for free-flying birds. However, wing-clipping should be avoided, except in rare situations where it improves bird welfare, and the process needs to be carried out correctly with the trim being functional and appropriate to the species of bird [ 39 ]. For example, asymmetric trimming can lead to major welfare problems.…”
Section: Animal Welfarementioning
confidence: 99%
“…The measurement of feather corticosterone concentration ( fCORT ) is a comparatively new and increasingly used method in stress research in wild and captive birds as well as in poultry ( Carbajal et al, 2014 ; Romero and Fairhurst, 2016 ; Häffelin et al, 2020 ; Leishman et al, 2020 ; Monclús et al, 2020 ; Reese et al, 2020 ). Numerous studies have reported a stable incorporation of corticosterone in feathers and a positive correlation between corticosterone concentrations in feathers and in peripheral blood ( Bortolotti et al, 2008 ; Romero and Fairhurst, 2016 ).…”
Section: Introductionmentioning
confidence: 99%